2017
DOI: 10.1108/ijopm-01-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

The company-customer transfer of logistics activities

Abstract: International audiencePurposeThe starting point of the paper is the fact that customers participate in the logistics activities of the supply chain (SC) (Johnston, 1989; Granzin and Bahn, 1989). Having established that customers can and do participate in logistics, firms can consider transferring some of their logistics activities to/from their customer. The transfer can take two contrasting forms: outsourcing by the company of some logistics activities to its customers or insourcing by the company of some log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…While these studies establish the relevancy of the CP concept to the logistics services, more empirical evidence is needed to strengthen its saliency. Essentially, consumers do participate in logistics activities in various forms (Rouquet et al, 2017). In fact, the notion of consumer logistics was proposed several decades ago by Granzin and Bahn (1989).…”
Section: Consumer Logisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…While these studies establish the relevancy of the CP concept to the logistics services, more empirical evidence is needed to strengthen its saliency. Essentially, consumers do participate in logistics activities in various forms (Rouquet et al, 2017). In fact, the notion of consumer logistics was proposed several decades ago by Granzin and Bahn (1989).…”
Section: Consumer Logisticsmentioning
confidence: 99%
“…As a central theme in the CP literature, consumers' motivation to participate is of particular interest to our study (Rouquet et al, 2017). To this end, the logistics literature focuses on delivering services with a superior quality in order to improve customers' satisfaction and loyalty (Mentzer et al, 2001;Rao et al, 2011).…”
Section: Cognitions and Affects As Motivatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outsourcing Explore the different ways in which outsourcing can manifest itself, such as insourcing vs outsourcing (Rouquet et al, 2017) Examine how outsourcing is shaped by specific phenomena, such as conventions to make sense of work packages (Oshri et al, 2018) and organizational resources and capabilities (Malik et al, 2018) 2…”
Section: Case Study Researchmentioning
confidence: 99%
“…A key issue for companies in the transfer process is the need to redesign their SC in transportation, warehousing and production. Customer engagement logistics is a key variable in SC design [ 9 ]. The purchasing manager found that the shared responsibility was to positively influence the delivery speed of the supplier, while the logistics manager found that it had a positive impact on the supplier’s price performance.…”
Section: Introductionmentioning
confidence: 99%